Prolongation of survival of dogs with oral malignant melanoma treated by en bloc surgical resection and adjuvant CSPG4‐antigen electrovaccination. (4th May 2016) - Piras, L. A.; Riccardo, F.; Iussich, S.; Maniscalco, L.; Gattino, F.; Martano, M.; Morello, E.; Lorda Mayayo, S.; Rolih, V.; Garavaglia, F.; De Maria, R.; Lardone, E.; et al.
Abstract: Reported post‐surgery 1‐year survival rate for oral canine malignant melanoma (cMM) is around 30%; novel treatments are needed as the role of adjuvant chemotherapy is unclear. This prospective study regards adjuvant electrovaccination with human chondroitin sulfate proteoglycan‐4 (hCSPG4)‐encoded plasmid in 23 dogs with resected II/III‐staged CSPG4‐positive oral cMM compared with 19 dogs with resected only II/III‐staged CSPG4‐positive oral cMM. Vaccination resulted in 6‐, 12‐, 18‐ and 24‐month survival rate of 95.6, 73.9, 47.8 and 30.4%, respectively [median survival time (MST) 684 days, range 78–1694, 8 of 23 dogs alive] and 6‐, 12‐, 18‐ and 24‐month disease‐free interval (DFI) rate of 82.6, 47.8, 26.1 and 17.4%, respectively (DFI 477 days, range 50–1694). Non‐vaccinated dogs showed 6‐, 12‐, 18‐ and 24‐month survival rate of 63.2, 26.3, 15.8 and 5.3%, respectively (MST 200 days, range 75–1507, 1 of 19 dogs alive) and 6‐, 12‐, 18‐ and 24‐month DFI rate of 52.6, 26.3, 10.5 and 5.3%, respectively (DFI 180 days, range 38–1250). Overall survival and DFI of vaccinated dogs was longer in those <20 kg. In vaccinated and non‐vaccinated dogs local recurrence rate was 34.8 and 42%, respectively while lung metastatic rate was 39 and 79%, respectively.